2022
DOI: 10.2991/978-94-6463-026-8_30
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Information Quality and Experience Quality on Trust and Its Impact on Customer Loyalty

Abstract: This study aims to determine the effect of information provided by mobile applications and experiences in using mobile applications on the trust in the use of mobile applications and their impact on the loyalty of the use of mobile applications Explanatory research employing a quantitative methodology, in this case by way of directly polling users of mobile applications is the kind of study that falls under this category. The survey was conducted using an online questionnaire to 315 respondents who were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(21 reference statements)
0
0
0
1
Order By: Relevance
“…Likewise, Şahin & Güzel (2020) found that tourist emotional arousal experience positively influences post-experience behaviour. On the other hand, the results of the indirect effect confirm customer perceived value does not fully mediate the relationship between aroused experience and customer loyalty (Patma et al, 2020). Likewise, customer perceived value through service quality influences destination image and behavioural intention (Moon et al, 2013).…”
Section: The Mediation Test For Both Direct and Indirect Effects With...mentioning
confidence: 85%
See 1 more Smart Citation
“…Likewise, Şahin & Güzel (2020) found that tourist emotional arousal experience positively influences post-experience behaviour. On the other hand, the results of the indirect effect confirm customer perceived value does not fully mediate the relationship between aroused experience and customer loyalty (Patma et al, 2020). Likewise, customer perceived value through service quality influences destination image and behavioural intention (Moon et al, 2013).…”
Section: The Mediation Test For Both Direct and Indirect Effects With...mentioning
confidence: 85%
“…Perceived quality from(Tsai & Wang, 2016);(Bae & Jeon, 2022) and was measured with 6 items. Customer-perceived value indicators were adopted fromPatma et al (2020) and were measured with 8 items.…”
mentioning
confidence: 99%
“…1 -20 ketersediaan, dan kelengkapan konten informasi. Menurut (Patma et al, 2023), kualitas informasi menonjol sebagai penentu paling penting dari kepuasan pelanggan online. Tingkat kualitas informasi yang lebih tinggi yang dihasilkan oleh sistem informasi berkorelasi dengan peningkatan substansial dalam kepuasan pelanggan.…”
Section: Information Quality Tidak Berpengaruh Terhadap Customer Sati...unclassified